2004
DOI: 10.4315/0362-028x-67.1.142
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Radiation-Induced Hydrocarbons and 2-Alkylcyclobutanones from Dried Shrimps (Penaeus aztecus)

Abstract: We investigated the usefulness of hydrocarbons and 2-alkylcyclobutanones as markers for irradiated, dried shrimps. A method was developed to detect the irradiation of dried shrimps (Penaeus aztecus) by identifying radiation-induced hydrocarbons and 2-alkylcyclobutanones extracted from dried shrimps, which were separated by Florisil column chromatography and identified by a method using gas chromatography/mass spectrometry. Radiation-induced hydrocarbons and 2-alkylcyclobutanones are formed from the fatty acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Kim et al (2004a), using a method very similar to EN1785, did not provide detection limits but reported low levels (0.014 mg/kg) of 2-DCB in irradiated dried shrimp and lower levels (0.006 mg/kg) of 2-TCB although these would be higher when presented on a wet weight basis. Blanch et al (2009) using SPME-GC-MS found a limit of detection of 0.3 mg/kg 2-DCB.…”
Section: Detection Limitmentioning
confidence: 87%
See 1 more Smart Citation
“…Kim et al (2004a), using a method very similar to EN1785, did not provide detection limits but reported low levels (0.014 mg/kg) of 2-DCB in irradiated dried shrimp and lower levels (0.006 mg/kg) of 2-TCB although these would be higher when presented on a wet weight basis. Blanch et al (2009) using SPME-GC-MS found a limit of detection of 0.3 mg/kg 2-DCB.…”
Section: Detection Limitmentioning
confidence: 87%
“…The irradiation dose varies with application. Ionising radiation induces the formation of a variety of hydrocarbons and 2-ACBs from lipids (Kim et al, 2004a). Their formation was first reported by Le Tellier and Nawar (1972) who irradiated triacylglycerols (triglycerides) at a high dose (60 kGy).…”
Section: Formation Of 2-acbsmentioning
confidence: 99%
“…The processed food with ionizing radiation induces the formation of various by‐products such as free radicals, hydrocarbons, and 2‐ACBs that are generated as a result of radiolysis triglycerides, phospholipids, and fatty acids present in the food (Kim and others ; Sommers and others ). It is reported the 1st time by Letellier and Nawar ().…”
Section: Formation Of 2‐acbsmentioning
confidence: 99%
“…The food irradiation processing is performed by using accelerated electron beams, X‐rays, or gamma radiation ( 60 Co or 137 Cs). Ionizing radiation induces the formation of a variety of hydrocarbons, and 2‐Alkylcyclobutanones (2‐ACBs) (Kim and others ). Treatment performed by the radiation when used for a purpose of reducing the microbial burden inhibit cell division in microorganisms, thereby promoting molecular structural change, then once absorbed by the biological material, the gamma radiation develops a direct and indirect impact on the material that received this treatment, thus performing disinfection function (Fanaro and others ).…”
Section: Introductionmentioning
confidence: 99%
“…The European Norm (EN) 1785 method (16), as a standard 2-ACB detection method, has proven applicable for a wide range of irradiated fat-containing foods, such as chicken (17,18), cured pork (19), liquid whole egg (20), Camembert cheese (21), fruits (21,22), and seafood (23,24). However, this method is a complex procedure involving a long Soxhlet extraction of 2-ACBs from the sample (6 h), followed by large-scale column chromatography (overall analysis time of 72 h).…”
Section: Introductionmentioning
confidence: 99%